Carbon storage potential in degraded forests of Kalimantan, Indonesia. (21st August 2018) - Ferraz, António; Saatchi, Sassan; Xu, Liang; Hagen, Stephen; Chave, Jerome; Yu, Yifan; Meyer, Victoria; Garcia, Mariano; Silva, Carlos; Roswintiart, Orbita; Samboko, Ari; Sist, Plinio; et al.
Abstract: The forests of Kalimantan are under severe pressure from extensive land use activities dominated by logging, palm oil plantations, and peatland fires. To implement the forest moratorium for mitigating greenhouse gas emissions, Indonesia's government requires information on the carbon stored in forests, including intact, degraded, secondary, and peat swamp forests. We developed a hybrid approach of producing a wall-to-wall map of the aboveground biomass (AGB) of intact and degraded forests of Kalimantan at 1 ha grid cells by combining field inventory plots, airborne lidar samples, and satellite radar and optical imagery. More than 110 000 ha of lidar data were acquired to systematically capture variations of forest structure and more than 104 field plots to develop lidar-biomass models. The lidar measurements were converted into biomass using models developed for 66 439 ha of drylands and 44 250 ha of wetland forests. By combining the AGB map with the national land cover map, we found that 22.3 Mha (10 6 ha) of forest remain on drylands ranging in biomass from 357.2 ± 12.3 Mgha −1 in relatively intact forests to 134.2 ± 6.1 Mgha −1 in severely degraded forests. The remaining peat swamp forests are heterogeneous in coverage and degradation level, extending over 3.62 Mha and having an average AGB of 211.8 ± 12.7 Mgha −1 . Emission factors calculated from aboveground biomass only suggest that the carbon storage potential of more than 15 Mha of degraded and secondary dryland forests will be about 1.1 PgC.